Informação, comunicação e sociabilidade via Internet: um estudo das interações no ciberespaço entre membros do Movimento Escoteiro - Adriana Bogliolo Sirihal (2005)
There has been a lot of discussion about the concept of information and the objectives of Information Science. This dissertation discusses the theme, presenting the approaches of different authors, and proposes an information cycle composed of communication, information, knowledge and development. The cycle is affected when communication occurs in cyberspace. The use of the Internet alters the course, speed, volume and distances involved in the information cycle. It also causes changes in social relations among individuals. The consequences of Internet use by scouts is the main theme of the research. The Scout Movement, defined by its founder as the art or the science of acquiring information is an educational organization which, among other characteristics, proposes the building of the character of children and young people through interaction with nature. The main objective of this study was to analyze the way Internet use has been influencing communication, information transfer and sociability at the different levels of the Scout Movement in the Metropolitan Area of Belo Horizonte. In order to achieve this goal, Internet sites created by Scout Groups have been evaluated. A questionnaire has been filled in by scouts from eleven Scout Groups of the Metropolitan Area of Belo Horizonte. Electronic messages posted to the official Metropolitan Scout Discrict discussion list have been analyzed. The focus groups technique has been used to make scouts debate the main topics to be investigated. The survey results indicated the growing use of the Internet and showed that it proposes new ways of social interaction, it helps understand scoutsprinciples and goals, and above all, it helps preserve their unity and objectives just as it divulges the different aspects the Movement acquires in view of the several cultural contexts of the places where it establishes itself.